Introducción. “Cefalópodos del estado”: Beckett y biopolítica. - Seán Kennedy (Estudios Irlandeses, 2019)
Beckett studies has changed, and changed utterly, in the last twenty years, extending its preoccupation with humanist philosophies to an engagement with history and politics. In the process, the inscrutable aspect of Beckett’s views on a range of political subjects has diminished. Emilie Morin’s Beckett Political Imagination (2017) provides ample evidence of his engagement with politics, while James McNaughton’s Samuel Beckett and the Politics of Aftermath (2018) extends the achievement of earlier accounts of his political aesthetic (e.g. Adorno, Boxall, Jones). One area of scholarship that has proved exceptionally fertile, if that is the right phrase, is biopolitics. Foucault’s identification of a new regime of power predicated on the management of populations, as distinct from individuals, is indispensable to an account of Beckett’s political bodies, as this volume confirms.